2009
DOI: 10.1038/nn.2327
|View full text |Cite
|
Sign up to set email alerts
|

Ube3a is required for experience-dependent maturation of the neocortex

Abstract: Experience-dependent maturation of neocortical circuits is required for normal sensory and cognitive abilities, which are distorted in neurodevelopmental disorders. We have tested whether experience-dependent neocortical modifications require Ube3a, an E3 ubiquitin ligase whose dysregulation has been implicated in autism and Angelman syndrome (AS). Using visual cortex as a model, we demonstrate that experience-dependent maturation of excitatory cortical circuits is severely impaired in AS mice deficient in Ube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
300
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(334 citation statements)
references
References 48 publications
(60 reference statements)
27
300
0
2
Order By: Relevance
“…Although Prader-Willi syndrome arises from loss of paternally expressed genes in this region, Angelman syndrome arises from the loss of a single gene, ube3a, the gene encoding maternally expressed ubiquitin protein ligase E3A, which is imprinted only in the brain (Abrahams and Geschwind, 2008). Ube3a is required for maintaining plasticity during experience-dependent neocortical development, consistent with the notion that loss of neocortical plasticity contributes to the cognitive deficits associated with Angelman syndrome (Yashiro et al, 2009).…”
Section: Comorbidity With Autismsupporting
confidence: 70%
“…Although Prader-Willi syndrome arises from loss of paternally expressed genes in this region, Angelman syndrome arises from the loss of a single gene, ube3a, the gene encoding maternally expressed ubiquitin protein ligase E3A, which is imprinted only in the brain (Abrahams and Geschwind, 2008). Ube3a is required for maintaining plasticity during experience-dependent neocortical development, consistent with the notion that loss of neocortical plasticity contributes to the cognitive deficits associated with Angelman syndrome (Yashiro et al, 2009).…”
Section: Comorbidity With Autismsupporting
confidence: 70%
“…Loss of UBE3A expression in axon terminals during early stages of postnatal development could potentially lead to wiring defects in AS model mice. Overexpression of the putative UBE3A substrate Ephexin 5 suppresses excitatory synapse formation in developing hippocampal neurons (Margolis et al, 2010), in general agreement with electrophysiological correlates of reduced excitatory synapse number in AS mice (Yashiro et al, 2009;Greer et al, 2010;Wallace et al, 2012). Although Ephexin 5 is expressed in axons and could presumably inhibit excitatory synapse formation via a presynaptic effect, this reduction has been ascribed to postsynaptic functions of Ephexin 5 (Margolis et al, 2010).…”
Section: Ube3a In Synapsessupporting
confidence: 68%
“…Mouse models of AS carry maternally-inherited Ube3a deletions, and display many Angelman-like phenotypes, including learning and memory deficits, motor dysfunction, and seizures (Jiang et al, 1998;Miura et al, 2002;van Woerden et al, 2007;Heck et al, 2008;Jiang et al, 2010;Mulherkar and Jana, 2010;Margolis et al, 2015). At the cellular level, AS mice exhibit abnormalities in synaptic transmission and plasticity (Weeber et al, 2003;van Woerden et al, 2007;Yashiro et al, 2009;Greer et al, 2010;Margolis et al, 2010;Wallace et al, 2012), Golgi acidification (Condon et al, 2013), and mitochondrial function Llewellyn et al, 2015;Santini et al, 2015) . This phenotypic diversity suggests a multiplicity of roles for UBE3A in neural function.…”
mentioning
confidence: 99%
“…Consistent with Ube3a playing an important role in synaptic function, electrophysiological experiments have demonstrated that long-term potentiation and long-term depression are impaired in the hippocampus and neocortex of mice with AS [35,42,47,49,50]. Additionally, studies implicate Ube3a in experience-dependent visual cortical plasticity [47]. Other studies have found that deletion of Ube3a also leads to changes in inhibitory synapse function [51].…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 84%
“…Ube3a-deficient mouse brains exhibit reduced density of dendritic spines (the location of >95 % of excitatory synapses) in both hippocampal and neocortical neurons [47,48]. Consistent with Ube3a playing an important role in synaptic function, electrophysiological experiments have demonstrated that long-term potentiation and long-term depression are impaired in the hippocampus and neocortex of mice with AS [35,42,47,49,50]. Additionally, studies implicate Ube3a in experience-dependent visual cortical plasticity [47].…”
Section: Cellular and Molecular Underpinnings Of Asmentioning
confidence: 89%